AJUSTE DEL MODELO DE MOKKEN CON EL PROGRAMA MSP 4.0: UNA APLICACION CON ITEMS DE RAZONAMIENTO INDUCTIVO NUMERICO - Rivas Moya, Teresa (R.E.M.A. Revista electrónica de metodología aplicada, 2012)
From relatively weak assumptions, the Nonparametric monotone IRT of Mokken gives an order to the subjects and/or items. The parameters and Functions of Items Response for dichotomous items satisfying Monotone Homogeneity (MH ó HM) and Double Monotony (DM) are defined. The neccessary assumptions which must satisfy a set of monotonely homogeneous (MH) or doubly monotone (DM) items, methods for the evaluation of goodness of fit of these models, and procedures to obtain reliability of a set of DM items are given. The model is fitted with the program 'Mokken Scale Analysis for Polytomous Ítems' (MSP 4.0) of Molenaar, Debets, Sijtsma y Hemker (1994). An application is also made from the answers given by a sample of 400 subjects to 12 dichotomous items of numerical inductive reasoning. The goodness of fit of DM model is proved. It is also shown that this set of items is a scale, and the order in which the set of items must be presented is also given. The set of items is invariant in subgroups of subjects, whose mean ages and standard deviations are similar. The subgroups are defined by several sociocultural levels in State, private, urban and rural schools. In addition, this accumulative scale is reliable.